Patterns and selected factors of change in college career decisions - Valmonte, Elnora Ll
This study sought to analyze the changes in college seniors' career decisions during their undergraduate years, with emphasis on the program changes and patterns of change occuring among the different career categories. The findings of the study showed that there were significantly more changers than non-changers. There were significant differences in the number of changes through the four years of college and in the different career categories. More changes occur during the first two years than during the last two years of college life. Students change to degree programs offering better job opportunities. The reasons why people transfer to another program or stay in their present program varies from person to person.